2011
DOI: 10.1002/mrm.22995
|View full text |Cite
|
Sign up to set email alerts
|

B Phase mapping at 7 T and its application for in vivo electrical conductivity mapping

Abstract: In this study, a new approach to measure local electrical conductivity in tissue is presented, which is based on the propagating B In recent years, the used frequency of radio frequency (RF) pulses in MRI has increased considerably as a consequence of the increase in magnetic field strengths. As an increased frequency leads to a shorter wavelength, the electromagnetic fields (EM-fields) induced by the RF pulse should more and more be regarded as waves (1,2) impinging onto a very dielectrically heterogeneous ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
235
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(238 citation statements)
references
References 24 publications
3
235
0
Order By: Relevance
“…Furthermore, exact knowledge of B + 1 phase is assumed. In practice, however, measurements of the B + 1 phase are based on assumptions regarding the object and coil geometry [3,4].…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, exact knowledge of B + 1 phase is assumed. In practice, however, measurements of the B + 1 phase are based on assumptions regarding the object and coil geometry [3,4].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Van Lier et al [4] demonstrated the feasibility of EPT using phase only information and Sodickson et al [5] introduced the so-called Local Maxwell Tomography (LMT) technique, which is free of assumptions on the B + 1 phase. What these currently used methods have in common is that local field equations (Maxwell's equations or Helmholtz's equation) are used as a basis for tissue parameter retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel non-invasive technique called MREPT (Magnetic resonance electric properties tomography) was introduced for the measurement of electrical properties (12)(13)(14). MREPT yields quantitative values for conductivity and permittivity, determined at the MR Larmor frequency.…”
Section: Original Articlementioning
confidence: 99%
“…The multi-echo readout scheme removed the effect of B 0 inhomogeneity, allowing the B 1 + phase (TE = 0 phase) to be retrieved through linear least squares fitting of the phase values. The approximation that the B 1 + phase is half the value of the transceive phase value was used herein (13,19,20).…”
Section: Sequence -Image Acquisitionmentioning
confidence: 99%
“…In addition, conductivity reconstruction using only the B 1 + phase has been introduced (13) and widely used (14,15), however it can provide accurate conductivity values under the assumption that the spatial variation of B 1 + magnitude is negligible. For all these applications and measurements, the conductivity value is needed to be estimated under an acceptable error level.…”
Section: Introductionmentioning
confidence: 99%